Targeting transcription regulation in cancer with a covalent CDK7 inhibitor - Kwiatkowski, Nicholas (Nature, 2014)
Tumor oncogenes include transcription factors that co-opt the general transcriptional machinery to sustain the oncogenic state(1), but direct pharmacological inhibition of transcription factors has thus far proven difficult(2). However, the transcriptional machinery contains various enzymatic co-factors that can be targeted for development of new therapeutic candidates(3), including cyclin-dependent kinases (CDKs)(4). Here we present the discovery and characterization of the first covalent CDK7 inhibitor, THZ1, which has the unprecedented ability to target a remote cysteine residue located outside of the canonical kinase domain, providing an unanticipated means of achieving selectivity for CDK7. Cancer cell line profiling indicates that a subset of cancer cell lines, including T-ALL, exhibit exceptional sensitivity to THZ1. Genome-wide analysis in Jurkat T-ALL shows that THZ1 disproportionally affects transcription of RUNX1 and suggests that sensitivity to THZ1 may be due to vulnerability conferred by the RUNX1 super-enhancer and this transcription factor’s key role in the core transcriptional regulatory circuitry of these tumor cells. Pharmacological modulation of CDK7 kinase activity may thus provide an approach to identify and treat tumor types exhibiting extreme dependencies on transcription for maintenance of the oncogenic state.